Opportunities for Conservation Agriculture in the EU Common Agricultural Policy 2014-2020 - Basch, G. (2012)
In the past, many relevant European Union (EU) documents made reference to the environmental problems caused by agriculture. In those papers, the concept of Conservation Agriculture (CA) as a possible solution was either omitted or timidly named, although sustainable agriculture was proclaimed as an objective of the EU in the Amsterdam treaty in 1999. EU’s position regarding several worldwide environmental problems, i.e. climate change, water and soil threats, is well known. However, to which extent these positions will be reflected in EU agricultural and environmental policies and concrete and binding measures in all member states for the period of 2014-2020 is still an open question. Through its Common Agricultural Policy (CAP) EU claims to address the main concerns of its agriculture and rural development. In this context, EU launched a Communication (COM (2010) 672 final) named “The CAP towards 2020. Meeting the food, natural resources and territorial challenges of the future”. Based on this paper we analyse the deliverables that CA could provide to achieve the overall objectives established for the CAP in the horizon 2014-2020.